2006
DOI: 10.1590/s1516-635x2006000300003
|View full text |Cite
|
Sign up to set email alerts
|

Period of incubation and posthatching holding time influence on broiler performance

Abstract: The present study had the objective of investigating the performance of broilers housed immediately after hatching or after a 12 or 24 hour of post-hatching holding time. One thousand and six hundred male Ross 308 broiler chicks with an initial body weight of 46 grams were used. These chicks were distributed in a completely randomized experimental design with 5 treatments and 8 replications of 35 birds in each treatment. The treatments in this study consisted of the removal of chicks from the hatchery in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 19 publications
6
27
0
1
Order By: Relevance
“…However, the percentage BW gain during the first 7 d was 76.6%, 76.2%, and 74.1% for the early, middle, and late hatching groups, respectively, so that differences in initial hatching BW disappeared. All hatch time groups exhibited a similar BW, feed intake, and mortality at 41 d of age (Almeida et al, 2006). Pinchasov & Noy (1993) and Tong et al (2015) found that BW loss and yolk sac utilization were increased when chicks had extended holding period.…”
Section: Effect Of Hatching Time On Yolk Sac Percentage and Broiler Lmentioning
confidence: 84%
See 3 more Smart Citations
“…However, the percentage BW gain during the first 7 d was 76.6%, 76.2%, and 74.1% for the early, middle, and late hatching groups, respectively, so that differences in initial hatching BW disappeared. All hatch time groups exhibited a similar BW, feed intake, and mortality at 41 d of age (Almeida et al, 2006). Pinchasov & Noy (1993) and Tong et al (2015) found that BW loss and yolk sac utilization were increased when chicks had extended holding period.…”
Section: Effect Of Hatching Time On Yolk Sac Percentage and Broiler Lmentioning
confidence: 84%
“…Corless & Sell (1999) reported reduced BW associated with extended post-hatch holding, but these findings were not consistent with the data presented by Casteel et al (1994), who weighed each group of birds 43 d following placement on feed and water and reported no differences. Work with respect to hatch time and post-hatch holding has often differed in that chicks were placed as much or more than 24 h apart, but weighed on the same day subsequently in some experiments (Pinchasov et al, 1993;Vieira & Moran, 1999) or on the basis of days on feed in other studies (Almeida et al, 2006;Lamot et al, 2014;Dişa et al, 2015). Furthermore, holding chicks in the hatcher for 24 h has been reported to not clinically dehydrate chicks or affect live performance (Casteel et al, 1994;Joseph & Moran, 2005;Almeida et al, 2006;Lamot et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in weight gain of the broilers at 21 days due to the increase in sunflower cake levels in the diet probably occurred as a result of the increased fiber inclusion in the diet and the decreased villus:crypt ratio, hampering the use of dietary nutrients in the animals because the main nutrient absorption sites in broilers are the duodenum and jejunum (ALMEIDA et al, 2006), which were affected by the diets. Similar results were found by Moghassam et al (2012), who evaluated increasing levels of sunflower meal on the intestinal morphology of broilers and found that villus height was decreased and crypt depth increased in the duodenum and jejunum segments.…”
Section: Resultsmentioning
confidence: 99%